Hubungan Status Gizi Ibu Hamil Trimester II Dengan Anemia di BPM Erlina Herawati Tahun 2023 - Hutahaean, Nurmalina; Lestari, Indri; Sinamora, Lasria; Sembiring, Mediana Beru; Panjaitan, Polmaria Metawati (Medihealth: Jurnal Ilmu Kesehatan dan Sains, 2023)
Insufficient knowledge about anemia has an influence on health behavior, especially when a woman is pregnant, which will result in less than optimal health behavior for pregnant women to prevent pregnancy anemia. Pregnant women who have less knowledge about anemia can result in less consumption of foods containing iron during pregnancy due to their ignorance. To determine the relationship between third trimester pregnant women's knowledge about anemia and compliance with consuming Fe tablets, the population used was the population of all patients at BPM Mutiara Bunda, Lahat Regency in 2023, 30 third trimester pregnant women from March - May 2023. Research This is an analytic survey with a cross sectional research design. Retrieval of data using a questionnaire. The data was processed using univariate analysis using descriptive statistics and bivariate analysis using the Chi-square test. The results of the Chi-Square test analysis showed that the p value = 0.000, which means less than ? = 0.05, so it can be concluded that there is a significant relationship between the knowledge of pregnant women third trimester regarding anemia with adherence to consuming Fe tablets at BPM Mutiara Bunda, Lahat District, 2023.